Hepatitis A vaccination coverage among adolescents (13–17 years) in the United States, 2008–2016 - Nelson, Noele P. (Vaccine, 2018)
BACKGROUND: The hepatitis A (HepA) vaccine was recommended by the Advisory Committee on Immunization Practices (ACIP) incrementally from 1996 to 1999. In 2006, HepA vaccine was recommended (1) universally for children aged 12–23 months, (2) for persons who are at increased risk for infection, or (3) for any person wishing to obtain immunity. Catch-up vaccination can be considered. OBJECTIVE: To assess HepA vaccine coverage among adolescents and factors independently associated with vaccination administration in the US. METHODS: The 2008–2016 National Immunization Survey–Teen was utilized to determine 1 and ≥2 dose HepA vaccination coverage among adolescents aged 13–17 years. Factors associated with HepA vaccine series initiation (1 dose) were determined by bivariate and multivariable analyses. Data were stratified by state groups based on ACIP recommendation: universal child vaccination recommended since 1999 (group 1); child vaccination considered since 1999 (group 2); universal child vaccination recommendation since 2006 (group 3). RESULTS: In 2016, national vaccination coverage for 1 and ≥2 doses of HepA vaccine among adolescents was 73.9% and 64.4%, respectively. Nationally, a 40 percentage point increase in vaccination coverage occurred among adolescents born in 1995 compared to adolescents born in 2003. Nationally, the independent factors associated with increased vaccine initiation was race/ethnicity (Hispanic, American Indian/Alaskan Native, Asian), military payment source and provider recommendation for HepA vaccination (2008–2013). Living in a suburban or rural region, living in poverty (level <1.33–5.03), and absence of state daycare or school HepA requirement were common factors associated with decreased likelihood of vaccine initiation. CONCLUSIONS: Efforts to increase HepA vaccine coverage in adolescents in all regions of the country would strengthen population protection from hepatitis A virus (HAV).